Implementation of Good University Governance Governance Islamic Private Vocational School in Medan - Zulia Hanum; Iskandar Muda; Rina Bukit; Muhyarsyah Muhyarsyah (Journal of International Conference Proceedings (JICP), 2019)
The purpose of this study was to determine the effect of commitment to the performance of lecturers at Islamic Private Universities in the City of Medan. The research method used was a survey. The sample of this study was 90 PTS lecturers and was taken by random technique. From the results of the study, it can be concluded that: there is an influence on lecturer performance.